Diversidad del derecho a la información y su efecto divulgativo en universidades de América Latina / Diversity on the Right for Information and its Effects on the Information Disclosure in Latin –America Universities - ABELLO-ROMERO, Juan; MANCILLA, Claudio; VIANCOS, Patricio (Utopía y Praxis Latinoamericana, 2019)
RESUMEN Este artículo analiza el efecto de las normativas legales del derecho de información sobre sus niveles de divulgación en universidades latinoamericanas. Se propone un modelo que se estima mediante el método de mínimos cuadrados. Los resultados son coherentes con los planteamientos teóricos y muestran evidencia respecto de la relación positiva entre la regulación de los derechos de información de los países y los niveles de divulgación de información. Esto implica que es fundamental robustecer las normativas para efecto de tener mayores niveles de divulgación y con ello disminuir las asimetrías de información. ABSTRACT This article analyzes the effect of legal regulations on the right to access to information on the levels of disclosure of information of Latin American universities. An econometric model is proposed that is estimated using the least-squares method. The results are consistent with the theoretical approaches and show evidence regarding the positive relationship between the regulation of the information rights of the countries and the levels of disclosure of information. This implies that it is essential to strengthening legal regulations to have higher levels of dissemination and reduce information asymmetries.